2003
DOI: 10.1086/374846
|View full text |Cite
|
Sign up to set email alerts
|

Is Azithromycin the First‐Choice Macrolide for Treatment of Community‐Acquired Pneumonia?

Abstract: Combination treatment with a beta-lactam plus a macrolide may improve the outcome for elderly patients with community-acquired pneumonia (CAP). The prognoses and mortality rates for elderly patients with CAP who receive ceftriaxone combined with a 3-day course of azithromycin or a 10-day course of clarithromycin were compared in an open-label, prospective study. Of 896 assessable patients, 220 received clarithromycin and 383 received azithromycin. There were no significant differences between groups with regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
1
18
2
2
Order By: Relevance
“…A retrospective study (1997)(1998)(1999)(2000) from Spain examined 603 patients who were admitted with CAP and treated with combination therapy [62]. All of the patients received ceftriaxone.…”
Section: Are All Macrolides Equal?mentioning
confidence: 99%
“…A retrospective study (1997)(1998)(1999)(2000) from Spain examined 603 patients who were admitted with CAP and treated with combination therapy [62]. All of the patients received ceftriaxone.…”
Section: Are All Macrolides Equal?mentioning
confidence: 99%
“…14,15 The extended-spectrum macrolide antibiotic azithromycin is unique from other macrolide type antibiotics in that it tends to concentrate in the white blood cells, which gravitate toward the site of infection. The white blood cells lyse and release their contents, including azithromycin.…”
Section: Macrolidesmentioning
confidence: 99%
“…14 The authors suggested that a shorter treatment course with azithromycin may result in better compliance with therapy.…”
Section: Duration Of Treatmentmentioning
confidence: 99%
“…Concerning the microbiological causes of pneumonia, Streptococcus pneumoniae was the most prevalent pathogen in 9 studies (9,10,14,15,17,18,(26)(27)(28) and Mycoplasma pneumoniae was the most prevalent in 6 studies (13,20,(22)(23)(24)(25). Chlamydophila pneumoniae (12,29), Haemophilus influenzae (19), and Staphylococcus aureus (11) were the most common pathogens in the remaining studies. Of note is that 2 studies included exclusively patients with atypical pneumonia (23,24).…”
mentioning
confidence: 99%
“…Mortality. Pooling of studies with treatments approved by the FDA (13,17,18,28,29) showed that mortality was lower in the short-course treatment group than in the long-course treatment group (2.4% versus 5.2%) (1,634 patients, RR ϭ 0.54 [95% CI, 0.32 to 0.89]). Mortality was also lower among patients who received treatment for Յ6 days than among those who received treatment for Ն7 days when we pooled studies with both FDA-approved and non-FDA-approved treatments (9 clinical trials) (1.9% versus 3.6%) ( Fig.…”
mentioning
confidence: 99%